The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d0ce01259a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mono- and divalent extra-framework cations on the structure and accessibility of porosity in chabazite zeolites

Abstract: The differences in valence and size between extra-framework cations exert a significant effect on the nitrogen sorption ability in the synthesised chabazite zeolites (K-CHA, Cs-CHA, Ca-CHA, Ba-CHA, Sr-CHA and Zn-CHA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…This is consistent with the observation that frameworks with larger cations exhibit tighter crystallographic spacing and reduced porosities, as indicated by the PXRD results. All framework candidates showed comparable BET surface areas when measured with N 2 at 77 K, but these values were significantly lower than those from CO 2 isotherms (around 20 ± 5 m 2 g −1 , in line with previous research by Doan et al; 32 further details can be found in Figure S2). The highest surface area was achieved by candidates with Rb + (Figure 1d).…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the observation that frameworks with larger cations exhibit tighter crystallographic spacing and reduced porosities, as indicated by the PXRD results. All framework candidates showed comparable BET surface areas when measured with N 2 at 77 K, but these values were significantly lower than those from CO 2 isotherms (around 20 ± 5 m 2 g −1 , in line with previous research by Doan et al; 32 further details can be found in Figure S2). The highest surface area was achieved by candidates with Rb + (Figure 1d).…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…All framework candidates showed comparable BET surface areas when measured with N 2 at 77 K, but these values were significantly lower than those from CO 2 isotherms (around 20 ± 5 m 2 g –1 , in line with previous research by Doan et al; 32 further details can be found in Figure S2 ). The highest surface area was achieved by candidates with Rb + ( Figure 1 d).…”
Section: Resultssupporting
confidence: 90%
“…The sorption capacity was 2.17, 3.80, 3.77, 3.67, and 3.39 mg g –1 for K + , Cu 2+ , Mn 2+ , Zn 2+ , and Fe 2+ , respectively. Also, we observed a selectivity of sorption (Cu 2+ > Zn 2+ > Fe 2+ > Mn 2+ > K + ) based on physical-chemical parameters, such as load, hydration energy, and hydration radius. Thus, the lower adsorption of K + is related to its properties (i.e., a monovalent ion with higher radius and hydration energy).…”
Section: Resultsmentioning
confidence: 78%
“… 30 The SiO 4 and AlO 4 tetrahedra are connected by oxygen atoms. 31 Due to its unique pore and cage structure, LTA zeolite is used to adsorb guest molecules of specific sizes and shapes. 32 In this work, the RA molecules were adsorbed on the electrode surface using LTA zeolite.…”
Section: Introductionmentioning
confidence: 99%